ADAPTASI BEBERAPA VARIETAS PADI GOGO DI KABUPATEN BLORA - Joko Susilo; Widarto Jp Widarto Jp (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
Dry land is very potential for gogo (up land rice) paddy plantation because gogo paddy does not need some special requirements as the contrary to the low land rice needs. On marginal lands, where the level of fertility is low, and the climate is quite dry, the gogo paddy is able to grow and to produce well, as long as sufficient nurnberoffertilize is given. The research, with the purpose of getting new superior varieties of dry rice field in high result capacity compared with the variet• ies in farmers, has bees carried out in Bogem Village, Blora Regency in year 2003-2004. Seven superior varieties of dry rice field are Towuti, Limboto, Situ Patenggang, Situ Bagendit, Way Rarem, Danau Gaung, Cirata and IR64, as a standard variety of comparison are used as an experiment component, which is suitably arranged with a group random design, three reviews. In the locations of'Suntono, Limboto, Situ Bagendit, Cirata and Situ Patenggang give the results of 8.44; 7.42; 7.32, and 7. l 9 ton/hectare cach. lR64 produces only 6.08 ton/hectare. In the locations ofTogiman, Limboto and Situ Bagendit give the result of8.56 ton/hectare each. IR64 just produces 6.96 ton/hectare. For gogo varietas, Limboto and Situ Bagendit show superiority compared to Suntono and Togiman, in production